تفصيح اللهجة القاهرية في التراكيب والأصوات : دراسة وصفية وتحليلية - Asmaa Samsudin (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
The idea of this study is to show that not all that common people use in their conversation is considered a misconception. The study also to consider the Cairene dialect which still retains ancient Arabic words. Although most writers have abandoned it by doubting its eloquence, it is in fact filled with eloquent words. The aim of this study is to track the semantics in the vernacular structures of the Cairene dialect, referring to its origin in some classical Arabic dictionaries, and in books about Qur'anic readings as well as in contemporary scholarly works, focusing on the modifications and replacements which have occurred in Standard Arabic vocabulary in terms of structures and sounds, across the tongues of the Cairene people, whether by omission, addition, inversion or otherwise. This study also authenticates the eloquence of the Cairene dialect and the advantages of it, now that the Arabs in the Arab world think that the Cairene dialect has nothing to do with Standard Arabic language and that it only belongs to the Egyptians. As a matter of fact this dialect goes back to the roots of Standard Arabic language phonologically, syntactically, morphologically and semantically. The researcher used the descriptive approach to describe the essence of the Cairene dialect scientifically and accurately, starting from its history and formation as well as its prevalence and the influence it gained from other languages, also particularly talking about its syntax although it is not officially recognized nor is it used in writing scientific researches. The study also relied on the analytical method for the analysis of the structures and sounds contained in the Cairene dialect and taken from the social Egyptian movie, "A Legal Betrayal", semantically, morphologically and phonologically to achieve the desired objectives. Among the most important conclusions of this study is that the Cairene dialect is prepared to use correct eloquent words which probably would have been lost if not used, and to borrow authentic Arabic words to make different new meanings in addition to producing, by means of derivation, words needed by people in their daily lives, and this, in itself, would broaden the scope of eloquence and revive the language.